Do assentamento a universidade : a mulher camponesa no ensino superior. - Silva, Denice Batista da (2009)
Brazilian funds structure bequeathed to fieldworkers field and knowledge expropriation. It has been recaptured from man and woman organization, which together adds forces for fighting for tenure and for being entitled to the access to good public education. In this context, Pronera has been an access way to superior level to retired people in Brazil. In this work, built up connected to the post-graduation in education nucleus of the Federal University of Sergipe, on the line of study History, Society and Educational Thought , we analyze countrywoman agrarian reform areas insertion on superior education at the Federal University of Sergipe, at two courses: Agronomic Engineering and Land Pedagogy. This work is characterized as qualitative, exploratory, based on interviews, to which we had optioned for a dialectic approach because we understand that it makes us able to have a better comprehension of existent relation between knowledge and countrywoman workers emancipation. We identify woman concentration in courses typically female by making maps of ingress in special programs in north and northeast superior courses. Long distances from school, wedding and sons are some of what women may struggle to pursue education/formation process, nevertheless, in despite of arduousness to keep studying, they recognize that access to superior education and scientific knowledge contribute to their emancipation and make them powerful. More than ascertaining to woman equity on accessing education/formation, it is necessary giving them permanency circumstances aiming at their courses conclusion.